Clinical Evaluation of Severe Acute Respiratory Syndrome Coronavirus 2 Rapid Antigen Tests During the Omicron Wave in South Africa . (3rd August 2022) - Samsunder, Natasha; de Vos, Margaretha; Ngcapu, Sinaye; Giandhari, Jennifer; Lewis, Lara; Kharsany, Ayesha B M; Cawood, Cherie; de Oliveira, Tulio; Karim, Quarraisha Abdool; Karim, Salim Abdool; Naidoo, Kogieleum; Escadafal, Camille; et al.
Abstract: We evaluated the performance of nasal and nasopharyngeal Standard Q COVID-19 [coronavirus disease 2019] Ag tests (SD Biosensor) and the Panbio COVID-19 Ag Rapid Test Device (nasal; Abbott) against the Abbott RealTi m e severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) assay during the Omicron (clades 21M, 21K, and 21L) wave in South Africa. Overall, all evaluated tests performed well, with high sensitivity (range, 77.78%–81.42%) and excellent specificity values (>99%). The sensitivity of rapid antigen tests increased above 90% in samples with cycle threshold <20, and all 3 tests performed best within the first week after symptom onset. Abstract : The SD Biosensor and Panbio rapid antigen tests performed well in samples with Omicron 21M, 21K, and 21L infections. The Panbio test performed best in infections with Omicron 21L, which had significantly higher viral load than 21M and 21K.